Recovery of manganese oxides from spent alkaline and zinc-carbon batteries. An application as catalysts for VOCs elimination - Gallegos, María Victoria (2013)
Manganese, in the form of oxide, was recovered from spent alkaline and zinc–carbon batteries employing a biohydrometallurgy process, using a pilot plant consisting in: an air-lift bioreactor (containing an acid-reducing medium produced by an Acidithiobacillus thiooxidans bacteria immobilized on elemental sulfur); a leaching reactor (were battery powder is mixed with the acid-reducing medium) and a recovery reactor. Two different manganese oxides were recovered from the leachate liquor: one of them by electrolysis (EMO) and the other by a chemical precipitation with KMnO4 solution (CMO). The non-leached solid residue was also studied (RMO). The solids were compared with a MnOx synthesized in our laboratory. The characterization by XRD, FTIR and XPS reveal the presence of Mn2O3 in the EMO and the CMO samples, together with some Mn4+ cations. In the solid not extracted by acidic leaching (RMO) the main phase detected was Mn3O4. The catalytic performance of the oxides was studied in the complete oxidation of ethanol and heptane. Complete conversion of ethanol occurs at 200 °C, while heptane requires more than 400 °C. The CMO has the highest oxide selectivity to CO2. The results show that manganese oxides obtained using spent alkaline and zinc–carbon batteries as raw materials, have an interesting performance as catalysts for elimination of VOCs